MENELUSURI JEJAK PEMIKIRAN PENDIDIKAN K.H. AHMAD DAHLAN SEBAGAI FONDASI INOVASI PENDIDIKAN ISLAM MASA KINI - Asiana; Sri Juwita; Novrian Eka Safutra; Abu Mansur; Nurlaila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research examines the educational philosophy of K.H. Ahmad Dahlan and its role as a foundational reference for innovation in modern Islamic education. The study is motivated by contemporary issues in Islamic schooling, particularly the weakening of students’ character and the urgent need to harmonize religious teachings with modern scientific knowledge. The objective of this work is to explore Dahlan’s key educational principles, his instructional approaches, and their relevance in addressing present educational challenges. Employing a qualitative library research design, this study analyzes credible academic sources, including journal articles, books, and historical documentation. The results show that Dahlan highlighted the inseparability of religious and general sciences, promoted contextual interpretation of Qur’anic teachings, and emphasized character formation through exemplary conduct and real-life application of knowledge. His pedagogical strategies—such as contextual instruction, demonstration, and experiential learning—proved effective in developing students’ intellectual, ethical, and social competencies. The study concludes that Dahlan’s educational vision remains profoundly significant today, offering a holistic and adaptive framework that integrates cognitive growth, moral development, and social engagement. His ideas continue to provide a transformative model for Islamic education in responding to global changes while upholding essential moral and spiritual values.